Determination of mutagenicity of chemical compounds, physical factors and environmental pollutants by the Drosophila melanogaster wing somatic mutation and recombination test - L. P. Zakharenko; I. K. Zakharov (Вавиловский журнал генетики и селекции)
A somatic mutation and recombination test (SMART) on the wing cells of Drosophila melanogaster is described in this article in detail. SMART can be used to evaluate the effect of various factors on the genome: physical (temperature, various types of radiation, electromagnetic fields), biogenic (genetic, physiological, infectious factors) and a wide range of chemical compounds. SMART is used as an in vivo version of the method for evaluating promutagenic and mutagenic properties of food, food supplements, potential drugs and cosmetics, and environmental pollutants. The method is based on the influence of the agents under study on the dividing cells of the wing imaginal discs of larvae heterozygous for recessive mutations, marking the wing cells. The mutations, multi wing hairs (mwh; 3 – 0.3) and flare (flr; 3 – 38.8), are located on the left arm of chromosome 3. The Drosophila melanogaster wing contains 24,400 cells arranged in two layers. Each normal cell has only one wing fiber. Recombination or mutational events in the cell leads to the formation of mutant spots/clones visible by microscopic analysis of the wing surface. The Drosophila and mammalian detoxication system is arranged on similar principles, which are based on the action of cytochrome P450. There are modifications to SMART, based on elevated cytochrome P450 expression, allowing more reliable extrapolation of the test results to mammals. Detailed recommendations for the use of the SMART method on the wing cells of Drosophila melanogaster presented in the paper can be used as a textbook in practice and for training purposes.